Clinical Reasoning: A 32-Year-Old Woman With Tunnel Vision and Back Pain. (1st November 2022) - Primiani, Christopher T.; Hale, David E.; Shah, Manali; Green, Kemar E.
Abstract : The incidence of new onset visual disturbances in emergency departments across the country is frequent. A detailed history of events and thoughtful physical examination may produce a diagnosis; however, atypical cases may require further diagnostic testing to explain symptoms. We present a case of presumed increased intracranial pressure with atypical findings on diagnostic testing, which allowed our team to explore a broader differential diagnosis. This clinical reasoning article will benefit students, residents, and attendings alike to continue to uncover etiologies for symptoms of increased intracranial pressure and review differential diagnoses in similar presentations.